FROM TEACHING PROVIDERS TO KNOWLEDGE ENGINES: TRANSFORMING PRIVATE HIGHER EDUCATION IN ACEH AMID THE ARTIFICIAL INTELLIGENCE REVOLUTION - Chairul Bariah (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
The rapid advancement of Artificial Intelligence (AI) is fundamentally reshaping the global landscape of higher education, challenging established business models and modes of knowledge delivery. In Indonesia, Private Higher Education Institutions (PHEIs) serve a critical role in expanding access, yet they remain structurally vulnerable due to heavy reliance on tuition fees and a prevailing focus on instruction over inquiry. This article examines the existential challenges facing PHEIs, with specific focus on the post‑conflict, resource‑rich but economically constrained context of Aceh. It argues that the traditional model of “teaching factories” is no longer viable in an era where AI democratises information access. Instead, PHEIs must undergo a paradigm shift to become Knowledge Engines: institutions that treat research, faculty development, and community engagement as strategic investments rather than operational costs. Drawing on recent global literature and local contextual analysis, the study proposes a four‑pillar framework comprising problem‑centred local research, faculty empowerment as knowledge producers, integrated curricula, and strategic partnership development. The analysis demonstrates that by leveraging AI not merely for efficiency but to unlock local data and contextual insights, PHEIs can build unique competitive advantages that large public universities cannot easily replicate. This transformation is not only essential for institutional survival but also vital for ensuring that higher education contributes meaningfully to regional development, cultural preservation, and intellectual independence in Aceh and across Indonesia.